The Investigative Studies on the Adsorption Capacity of Zn (II) On Laterite Soil, Black Cotton Soil and Fullers Earth Soil - DENGI, Mallikarjun; R. Mise., Dr. Shashikant (PREPARE@u® | IEI Conferences, 2021)
Abstract - This study aimed to Adsorption of Zinc (II) Ions on White Soil, Laterite Soil Black Surface Soil is being studied by batch adsorption technology. The main objective of this study was to study the physicochemical properties of Fuller’s earth, laterite soils, and black cotton soils. Sensing of Zn(II) removal by adsorbent as a function of contact time adsorbent dose and pH. To study adsorption kinetics, heat tracing experiments and isothermal patterns.